Peranan tax avoidance dan good corporate governance terhadap cost of debt pada perusahaan property dan real estate yang tedaftar di Bursa Efek Indonesia - Dian Arista Amalia; Norman Duma Sitinjak (University of Merdeka Malang, 2020)
ABSTRACTCompanies cannot always rely on internal funds to finance operational activities. Often external funds are needed to support company activities. External sources that are often used are debt. The consequence of using debt is the cost of debt. Creditors use tax avoidance and Good Corporate Governance considerations in making loan decisions to debtors. This study examines the role of tax avoidance and good corporate governance on debt costs. The result of this research is that tax avoidance has a positive effect on cost of debt, while institutional ownership and audit committee have a significant negative effect on cost of debt.